THE EFFECT OF INFLATION AND UNEMPLOYMENT ON NPF IN ISLAMIC COMMERCIAL BANKS IN INDONESIA - Tsania Hayatun Thoyyibah; Faizal Amir (I-Finance Journal, 2024)
This research seeks to examine the influence of inflation and the number of unemployed people on the problematic financing (NPF) of sharia commercial banks. The monthly time period from 2012 to 2023 was used as secondary data in this study. The quantitative method of this study used the time series VAR method which was then transformed into VECM. The data used comes from secondary sources, namely Sharia Banking Statistics from the OJK which includes Problematic Financing data; Bank Indonesia reports accessed via its official website which includes inflation data; and information from the official website of the Central Statistics Agency (BPS) which provides open unemployment rate (TPT) data. Inflation and unemployment are the two main factors that influence Sharia Commercial Bank Non-Performing Financing in this analysis. Study findings indicate that non-performing financing of sharia commercial banks in the long and short term is positively influenced by unemployment and inflation. The conclusion is that there is a significant positive influence between inflation on NPF, the higher the inflation value, the higher the NPF value in Sharia Commercial Banks. Likewise, unemployment has a significant influence on NPF, so the higher the unemployment rate, the higher the NPF level.